TEACHING SEARCH ENGINE MARKETING THROUGH THE GOOGLE AD GRANTS PROGRAM. Issue 2 (4th May 2018) - Clarke, Theresa B.; Murphy, Jamie; Wetsch, Lyle R.; Boeck, Harold
Abstract : Instructors may find it difficult to stay abreast of the rapidly changing nature of search engine marketing (SEM) and to incorporate hands-on, practical classroom experiences. One solution is Google Ad Grants, a nonprofit edition of Google AdWords that provides up to $10, 000 monthly in free advertising. A quasi-experiment revealed no differences between students using Ad Grants and traditional AdWords to run campaigns. Google Ad Grants can be a relevant, experiential, and promising way to help students develop skills, while simultaneously benefiting nonprofit organizations. The authors provide guidance for obtaining a grant and offer approaches for incorporating grants into learning experiences.